Opportunities and risks of globalization: Bangladesh perspective - Jalil, Md. Abdul; Islam, Md. Zahidul; Islam, Md. Asraful (2020)
Nowadays, globalization has become a slogan in the field of international relations. Mainly it is a process of expanding trade and commerce in a borderless market. Globalization has produced a window of opportunity for more countries to join the mainstream of world economy. Globalization has created enormous opportunities for the countries as well as risk factors and no country are out of these. The aim of this paper is to identify the opportunities and risks of globalization in the context of Bangladesh and to provide some policy recommendations. It is a qualitative research. In identifying and interpreting data basically the secondary sources like books, journal articles, newspapers and reports of national and international organizations etc. were considered. Findings of the study reveals that although Bangladesh is initially benefitted from globalization, there are numerous risk factors that might halt the development of Bangladesh anytime. At the end, it is suggested that the government should take necessary steps regarding foreign policy, FDI, collaboration between public and private sector, poverty alleviation, technological development etc. to get the optimum benefit from globalization.